Hubungan Pengetahuan, Sikap, dan Keterpaparan Sumber Informasi dengan Perilaku Seksual Pranikah pada Remaja di SMPN 18 Tanjung Jabung Timur - Sayani Sayani (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
Adolescence occurs with physical changes which are marked by the appearance of signs of primary and secondary sex as well as psychological changes including emotional changes to become sensitive and the behavior of wanting to try new things. Risky sexual acts among adolescents were also found in Jambi Province, which had a percentage of the teenage population (15-24 years) of 92.04%. Jambi Province adolescents who engage in risky sexual acts (holding hands, being hugged by girlfriends, kissing on the lips, petting, intercouse) are 68.1%. All adolescent behavior that is caused by sexual desire with the opposite sex or the same sex is carried out without a formal husband and wife relationship, namely sexual behavior, the object of this sexual behavior can be an imaginary person, another person can even be himself. Premarital sexual behavior such as kissing, necking, petting, and intercrouse.This study used an observational analytic design with a cross sectional approach which was carried out at SMPN 18 Tanjung Jabung Timur, in October 2022. The total population was 137 respondents with a sample using Lemeshow as many as 38 respondents. Data analysis using chi-square.The results showed that there was a relationship between knowledge (p-value 0.021), attitude (p-value 0.004 and OR 2.010), and exposure to information sources (p-value 0.021 and OR 3.210) with premarital sexual behavior at SMPN 18 Tanjung Jabung Timur. The conclusion obtained in this study is that there is a relationship between knowledge, attitudes, and exposure to sources of information with premarital sexual behavior at SMPN Tanjung Jabung Timur.